[Akureyri Along Eyjafjörður] - Streng, Evelyn Fiedler (1975)
Photograph of Akureyri along Eyjafjörður. The town sits along the water in a small cluster. Green and snowy mountains cover the background, obscured by white clouds. A brown, dirt hill covered in rock is sat at the bottom right corner of the photograph, a road visible past it to the right.